KAIVALYA: PROMOTING FINANCIAL INDEPENDENCE AMONG DIFFERENTLY ABLED IN KOTTAYAM DISTRICT - Biji Jose; S., Muthulakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In an era marked by dynamics and uncertainty, ensuring financial stability and secure sources of income is crucial. Self-employment offers a powerful avenue for achieving personal freedom and empowerment, fostering a vibrant and resilient economy driven by entrepreneurship and innovation. The Kaivalya Self-Employment Scheme, an employment rehabilitation initiative under the National Employment Service (Kerala), aims to support differently-abled individuals to undertake entrepreneurial activities. Despite existing legal provisions and awareness campaigns, many differently-abled persons still face significant barriers to employment. This paper explores the transformative potential of entrepreneurship for differently-abled individuals, focusing on selected case studies from the Kottayam district of Kerala, India. By examining the journeys of four differently-abled entrepreneurs, the study highlights the challenges they faced and the key role of the Kaivalya Self-Employment Scheme in their transitions. The success stories of existing beneficiaries can serve as powerful testimonials, inspiring others to pursue self-employment and thereby enhancing the scheme’s impact. The stories excels the importance of proactive government and agency efforts to raise awareness and ensure the full utilization of such schemes. Furthermore